Identification of Aroma Gene (Mutated badh2) and Properties of Aroma on Aromatic BC5F2 Ciherang - Jap Mai Cing; Djarot Sasongko Hami Seno; Tri Joko Santoso (Current Biochemistry, 2015)
Aromatic rice varieties have some weaknesses such as low productivity, and less resistant to pests and diseases. This study aimed to obtain homozygous strain of BC5F2 Ciherang aromatic through the identification of aroma gene (mutated badh2) and properties of the aroma. Ciherang paddy (nonaromatic paddy) was used as the female parent, whereas Mentik Wangi paddy (aromatic paddy) was used as the male parent. The experiment was conducted in BC5F2 because it is expected to generate plants with properties 98.4% close to female parent. The DNA from five strains of paddy plants BC5F2Ciherang X Mentik Wangi was isolated by a modified CTAB method. The concentration of DNA was determined by measuring absorbance at 260 nm wavelength, while its purity was determined from the ratio of the absorbance at a wavelength of 260/280 nm. PCR-based molecular selection was done by using the Bradbury primers. PCR results showed that of the 250 samples, there were 66 samples had DNA fragment of the same size as that of Mentik Wangi, i.e. 257 bp, 67 samples had the same size as the DNA fragment of Ciherang, i.e. 355 bp, and 117 samples had the same size with the both of DNA fragments, i.e. 257 bp and 355 bp. Plants with amplified 257 bp DNA fragment was subjected to leaf aroma test using 1.7% KOH. The results showed that 42 positive samples, out of 66 samples. Samples positive on leaf aroma test were tested again on rice aroma test. Rice aroma test results showed the majority (85.4%) samples that are positive on leaf aroma test is also positive on the rice aroma test.